2017
DOI: 10.1017/dmp.2017.63
|View full text |Cite
|
Sign up to set email alerts
|

Noncommunicable Diseases After the Great East Japan Earthquake: Systematic Review, 2011–2016

Abstract: NCDs pose major health issues after large-scale disasters. Establishment of strong countermeasures against interruption of treatment and surveillance systems to ascertain medical needs for NCDs are necessary to prepare for future disasters. (Disaster Med Public Health Preparedness. 2018; 12: 396-407).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 145 publications
(244 reference statements)
2
32
0
1
Order By: Relevance
“…Although the Brazzaville Declaration (WHO 2011) includes mental health issues in NCDs, we separated the mental health module from the NCD module for this study because it requires specific care. Previous literature search revealed 72 articles related to exacerbation of psychiatric disease that newly developed after GEJE, such as post-traumatic stress disorder (PTSD), depression, anxiety, and sleep deprivation (Murakami et al 2018). In the present study, sleep deprivation was the most frequent diagnosis (Table 1).…”
Section: Mental Health Issuesmentioning
confidence: 57%
See 1 more Smart Citation
“…Although the Brazzaville Declaration (WHO 2011) includes mental health issues in NCDs, we separated the mental health module from the NCD module for this study because it requires specific care. Previous literature search revealed 72 articles related to exacerbation of psychiatric disease that newly developed after GEJE, such as post-traumatic stress disorder (PTSD), depression, anxiety, and sleep deprivation (Murakami et al 2018). In the present study, sleep deprivation was the most frequent diagnosis (Table 1).…”
Section: Mental Health Issuesmentioning
confidence: 57%
“…Most diagnoses were continuous or newly developed NCDs in people in their 40s or older. Patients with NCD faced difficulties of continuing medical treatment, access to prescribed medications, poor living environment, stress, and lack of nutritious food and exercise opportunities (Murakami et al 2018). The most frequent NCD-related diagnosis was cardiovascular disease including hypertension (28%).…”
Section: Ncdmentioning
confidence: 99%
“…Risk factors regarding HTN include age, low fitness, tobacco consumption, unhealthy diet, high salt intake, and mental stress (35)(36). As far as we know, only one systematic review study (without meta-analysis) has addressed NCDs subsequent to the occurrence of a major disaster at time of Great East Japan Earthquake (37). Due to importance of the issue and lack of comprehensive review in this regard in the literature, the aim of this study was to present a systematic review and meta-analysis to evaluate the prevalence of DM and HTN following the occurrence of natural and man-made disasters that impose a lot of economic and psychological burdens on human societies.…”
Section: Introductionmentioning
confidence: 99%
“…A systematic review revealed psychological burdens such as a deterioration in mental health [21] and an increase in prevalence of post-traumatic stress disorder (PTSD) [22], as well as deterioration in health due to living in an evacuation center or a worse living environment [23], an increase in frailty risk [24], spread of pneumonia [25], and an increase in the number of people with subjective symptoms such as gastrointestinal and/or musculoskeletal symptoms [26].…”
Section: Factors Causing Increase In Long-term Care Certification Ratmentioning
confidence: 99%